PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS BARANG TIDAK SESUAI PESANAN DI MARKETPLACE ZALORA - Ardila, Revi; Setianingrum, Reni Budi (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
In today's era of globalization, everyone has the convenience of accessing everything, one of which is online buying and selling transactions (e-commerce). Marketplace is one of the forms of e-commerce development. The content in the marketplace itself has a wide variety of products and prices accompanied by specifications of the product conditions offered. However, due to the absence of direct meetings, there are often negligence and fraud committed by business actors to consumers which of course is very detrimental to consumers. In advertising products on the marketplace, sellers must provide detailed and accurate information about the goods sold in order to fulfill consumer rights. Consumers who receive products that are not in accordance with their orders can be caused by negligence or fraud by business actors. This study aims to examine legal protection and legal consequences if consumer rights are not fulfilled by business actors. The type of research used by the author is normative juridical by means of literature data collection and qualitative data analyst techniques.